Identification and Characterization of Black Carbon Aerosol Sources in the East Baltic Region - Steigvilė Byčenkienė; Vidmantas Ulevicius; Vadimas Dudoitis; Julija Pauraitė (Advances in Meteorology)
One-year continuous measurements of aerosol black carbon (BC) at the background site Preila (55°55′N, 21°00′E, 5 m a.s.l., Lithuania) were performed. Temporal and spatial evolution and transport of biomass burning (BB) and volcanic aerosols observed within this period were explained by the air mass backward trajectory analysis in conjunction with the fire detection data produced by the MODIS Rapid Response System and AERONET database. The surface measurements and analysis of the Angström exponent of the absorption coefficient done separately for shorter and longer wavelengths (i.e., α=370–520 nm and α=660–950 nm) showed that high levels of aerosol BC were related to the transport of air masses rich in BB products from Ukraine caused by active grass burning. During the events the highest mean values of the Angström exponent of the absorption coefficients α370–520 and α590–950 nm were observed (2.4±0.1 and 1.5±0.1, resp.). The ash plume of the Grimsvötn eruption on May 21, 2011 offered an exceptional opportunity to characterize the volcanic aerosols. The largest ash plume (in terms of aerosol optical thickness) over Lithuania was observed at May 24/25, 2011. The highest values of the Angström exponent of the absorption coefficients α370–520 and α590–950 nm were reached (1.3±0.1 and 1.4±0.1, resp.).